Pharmacological approaches to restore mitochondrial function - Andreux, Pénélope A. (2013)
Mitochondrial dysfunction is not only a hallmark of rare inherited mitochondrial disorders, but is also implicated in age-related diseases, including those that affect the metabolic and nervous system, such as type 2 diabetes and Parkinson’s disease. Numerous pathways maintain and/or restore proper mitochondrial function, including mitochondrial biogenesis, mitochondrial dynamics, mitophagy, and the mitochondrial unfolded protein response. New and powerful phenotypic assays in cell-based models, as well as multicellular organisms, have been developed to explore these different aspects of mitochondrial function. Modulating mitochondrial function has therefore emerged as an attractive therapeutic strategy for a range of diseases, which has spurred active drug discovery efforts in this area.